Frequency-specific modulation of motor cortical excitability by transcranial alternating current stimulation - Lei Tingting; Chen Lilin; Wang Chuangjia; Si Jiamen; Zhang Shuxian; Ai Yinan; Liu Hanjun; Zheng Haiqing (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Transcranial alternating current stimulation (tACS) is a non-invasive technique that modulates neural oscillations, yet its specific effects on cortical excitability are not well-understood. This study investigated the effects of tACS on neuroplasticity in the primary motor cortex (M1) across different frequencies. Methods In this randomized, sham-controlled, crossover study, 18 healthy young adults received β-tACS γ-tACS, and sham stimulation over the M1. Neurophysiological responses were assessed using motor evoked potentials (MEPs), electroencephalograms (EEG), and transcranial evoked potentials (TEPs) to determine the frequency-specific effects of tACS on cortical excitability and neuroplasticity. Results γ-tACS significantly enhanced cortical excitability, as reflected by larger MEP amplitudes compared to both β-tACS and sham stimulation. In addition, γ-tACS resulted in significantly smaller M1-P15 amplitudes in TEP than other stimulation conditions. In contrast, β-tACS did not produce significant changes in either MEPs or TEPs compared to sham stimulation. Conclusion These findings provide evidence that tACS induces frequency-dependent effects on cortical excitability and neuroplasticity within the M1. This selective modulation of cortical excitability with γ-tACS suggests its potential as a therapeutic intervention for optimizing motor function and rehabilitation. Trial registration This study was registered in the Chinese Clinical Trial Registry (ChiCTR2300074898, date of registration: 2023/08/18).